Obstacles of Micro and Small Business Access to Kredit Usaha Rakyat (KUR) Program - Eko Aristanto; Syarif Hidayatullah; Irany Windhyastiti; Umu Khouroh; Ike Kusdyah Rachmawati; Irany Windhyastiti (MBR (Management and Business Review), 2022)
This study aims to examine the obstacles of small and micro businesses in accessing credit business programs called Kredit Usaha Rakyat (KUR). The method of collecting data and information is done by desk documents and interviews with local government officials, personal banks implementing KUR, the poor who still cannot access microfinance and micro and small businesses, along with micro and small business actors who have obtained KUR in 9 districts/cities in Indonesia. The data analysis method uses descriptive analysis and Analytic Hierarchy Process (AHP). Based on the results of the AHP, access to services and KUR performance can be improved by taking into account several factors including: prospective debtor prospects, technical service capacity, policies and resources of banking, and macro factors. For research related to the future distribution of Kredit Usaha Rakyat (KUR), it is necessary to conduct an in-depth study of the impact on the development of micro and small businesses that receive KUR and increase the economic capacity of business actors who receive KUR.